"What will the doctor give me, the same painkiller?": a qualitative study exploring health-care seeking and symptoms self-management among patients for the treatment of long-term chikungunya disease, in Curaçao - Churnalisa Doran; Ashley Duits; Izzy Gerstenbluth; Adriana Tami; Ajay Bailey (BMC, 2023)
Abstract Background Long-term chikungunya disease, characterized by persistent disabling rheumatic symptoms, including poly-arthralgia/arthritis of severe pain intensity, can persist for years after infection with the re-emerging mosquito-borne chikungunya virus. Although persistent symptoms and pain severity are important determinants of health-care seeking and self-management of symptoms, research on these in relation to long-term chikungunya disease is scarce. This study aimed to explore the perceived benefits and perceived barriers concerning health-care seeking, based on the Health Belief Model, and the symptoms self-management strategies used for health outcome improvement among individuals affected by long-term chikungunya disease. Methods An exploratory qualitative descriptive study was conducted with 20 purposively selected adults (17 females and 3 males) with persistent rheumatic symptoms, recruited from an ongoing longitudinal chikungunya cohort, in Curaçao. Semi-structured interviews were carried out, audio-recorded, and transcribed. An iterative coding process was used for themes identification through inductive thematic analyses. Results No perceived benefits in health-care seeking were reported. Identified themes in relation to perceived barriers were: (1) health-care seeking at disease onset; (2) general practitioners (GPs) perceptions and awareness of persistent symptoms; (3) challenges for medical referrals and support; (4) no validation of symptoms and challenges accessing therapy; (5) health system restrictions; and (6) social stigmatization of psychological help. These perceived barriers have led participants to self-manage persistent symptoms. Over-the-counter pharmacological and/or non-pharmacological treatments were used without consulting GPs. Identified themes were: (1) self-medication of symptoms; and (2) self-management true non-pharmacological treatments. Conclusions To promote the benefits of long-term health-care seeking and subsequently reduce the possible harmful use of analgesics, a collaborative physician-patient therapeutic relationship need to be encouraged. To facilitate this, important shifts may be needed in chikungunya sequalae education of both patients and health-care professionals, and policy makers need to revise health systems for the long-term provision of multidisciplinary care to achieve beneficial health outcomes in long-term chikungunya disease.